Antifungal Streptomyces spp. Associated with the Infructescences of Protea spp. in South Africa - Human, Zander R.; Moon, Kyuho; Bae, Munhyung; de Beer, Z. Wilhelm; Cha, Sangwon; Wingfield, Michael J.; Slippers, Bernard; Oh, Dong-Chan; Venter, Stephanus N. (Frontiers in Microbiology, 2016)
Common saprophytic fungi are seldom present in Protea infructescences, which is strange given the abundance of mainly dead plant tissue in this moist protected environment. We hypothesized that the absence of common saprophytic fungi in Protea infructescences could be due to a special symbiosis where the presence of microbes producing antifungal compounds protect the infructescence. Using a culture based survey, employing selective media and in vitro antifungal assays, we isolated antibiotic producing actinomycetes from infructescences of Protea repens and P. neriifolia from two geographically separated areas. Isolates were grouped into three different morphological groups and appeared to be common in the Protea spp. examined in this study. The three groups were supported in 16S rRNA and multi-locus gene trees and were identified as potentially novel Streptomyces spp. All of the groups had antifungal activity in vitro. Streptomyces sp. Group 1 had inhibitory activity against all tested fungi and the active compound produced by this species was identified as fungichromin. Streptomyces spp. Groups 2 and 3 had lower inhibition against all tested fungi, while Group 3 showed limited inhibition against Candida albicans and Sporothrix isolates. The active compound for Group 2 was also identified as fungichromin even though its production level was much lower than Group 1. The antifungal activity of Group 3 was linked to actiphenol. The observed antifungal activity of the isolated actinomycetes could contribute to protection of the plant material against common saprophytic fungi, as fungichromin was also detected in extracts of the infructescence. The results of this study suggest that the antifungal Streptomyces spp. could play an important role in defining the microbial population associated with Protea infructescences.